The Influence of Vocational Theory Competency Test Results on Vocational Practice Competency Test Results - Koloway, Robyn; Ronga, Wendhel; Sumual, Herry; Olii, Djami; Takaredase, Agustinus (Department of Electrical Engineering Education, Faculty of Engineering, State University of Manado, 2024)
This study aims to determine how much the results of the theory of vocational competency tests are related to the results of the vocational practice competency tests of TITL students at SMK Negeri 2 Manado In addition this study also analyzed how relevant the vocational theory competency test material was to the vocational practice competency test material The method used in this study is a quantitative method with 56 students as research subjects In practice the researchers found that some students already understood electric motors and some did not understand when the researchers gave practice; as a result these students did not understand when the researcher or teacher was giving theory to them When researchers teach theory and practice they often provide post tests or questions for students to work on to see whether they comprehend correctly The results showed a positive and significant effect on the results of the vocational theory competency test and the results of the vocational practice competency test In addition the results of the analysis of the relevance of the material in the theory of vocational competency tests to the results of the vocational practice competency tests were 70 in the relevant category < p>